Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s10695-016-0322-3
|View full text |Cite
|
Sign up to set email alerts
|

Haemato-biochemical, non-specific immunity, antioxidant capacity and histopathological changes in Labeo rohita fingerlings fed rubber protein isolate

Abstract: A 60-day feeding trial was conducted to evaluate the haemato-biochemical, innate immune response, antioxidant capacity and histopathological changes in Labeo rohita fingerlings fed rubber protein isolates (RPI). One hundred and eighty fingerlings (average weight 4.45 ± 0.01 g) were distributed into five experimental groups in triplicate and fed with isonitrogenous and isocaloric diets. Soybean protein isolate (SPI) served as the reference diet (Control), and the treatment diets were formulated as RPI, RPI, RPI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 39 publications
2
32
0
Order By: Relevance
“…In tilapia fed with these feed, there were no significant differences in protein and lipid retention compared with controls (CTRL). In accordance with this, Suprayudi et al () and Fawole et al () had demonstrated that HCN reduction in feed ingredients will maintain protein and lipid retention rates in tilapia and rohu. This is due to the lower antinutritional factors that block the metabolic process and retain nutrients.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…In tilapia fed with these feed, there were no significant differences in protein and lipid retention compared with controls (CTRL). In accordance with this, Suprayudi et al () and Fawole et al () had demonstrated that HCN reduction in feed ingredients will maintain protein and lipid retention rates in tilapia and rohu. This is due to the lower antinutritional factors that block the metabolic process and retain nutrients.…”
Section: Discussionmentioning
confidence: 61%
“…This is seen from no significant differences in the case of specific growth rates of tilapia between treatments that include heated RSO feed (CPO: PRSO and PRSO). Previous research using the rubber seed‐based feed which has reduced the HCN levels has a similar specific growth rate and not significantly different from the control feed relatively (Deng et al, ; Fawole et al, ; Suprayudi et al, , ). The condition confirmed that these previous study results are in accordance with this current study.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations